The Representation of Indonesian Culture Diversity in English Textbooks Used in High School - Vira Zahara; Saraka; Desy Rusmawaty (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
In English language learning, textbooks play a crucial role since they provide knowledge about the English language and interrelated cultures. In Indonesia, the majority of schools are using textbooks which published by the Ministry of Education and Culture of Indonesia. Therefore, this study aimed to find how the English textbooks for high school represent Indonesian cultural diversity and how does the teacher perceived Indonesian cultural diversity presented in English textbooks. Those three English textbooks were published by the Ministry of Education and Culture of Indonesia. The design of this study was qualitative study that attempted to reveal the cultural categories in English textbooks. According to Yuen (2011) there are four cultural categories, Product, Person, Practice, and Perspective. In order to answer questions of the study, the researcher did content analysis. Regarding to cultural categories, this study found that in English textbook for 10th grade, Product dominated the cultural content with 50% or 78 appearances. Then, in English textbook for 11th, Person was the cultural categories that appeared most with 58% or 25 appearances. Lastly, English textbook for 12th grade also presented Person as the most cultural categories that appeared with 57% or 54 appearances. On the subject of perception of teacher toward Indonesian cultural diversity presented in English textbooks, this study also found that the teacher thought the cultural content in English textbook which published by the Ministry of Education and Culture of Indonesia still not enough to represent all Indonesian cultures. However, she agreed that those content are educated enough for the students